Pengaplikasian Semiotika Dalam Kajian Islam (Studi Analisis Kisah Nabi Yusuf) - Adam Maulana (JURNAL INDO-ISLAMIKA, 2011)
The presentation of the story in the Qur'an is always interrupted by religious advice. Stories are a very good method for teaching. The twists and turns of the journey of the Prophet Yusuf are told in Q.S. Joseph verses 1-111. In the story there are many lessons we can take. This paper will explain the story of the Prophet Joseph using Roland Barthes's semiotic approach. This writing data is sourced from books and journals that are relevant to the theme of the writing.